2010
DOI: 10.1186/1475-2859-9-56
|View full text |Cite
|
Sign up to set email alerts
|

Global expression studies in baker's yeast reveal target genes for the improvement of industrially-relevant traits: the cases of CAF16 and ORC2

Abstract: BackgroundRecent years have seen a huge growth in the market of industrial yeasts with the need for strains affording better performance or to be used in new applications. Stress tolerance of commercial Saccharomyces cerevisiae yeasts is, without doubt, a trait that needs improving. Such trait is, however, complex, and therefore only in-depth knowledge of their biochemical, physiological and genetic principles can help us to define improvement strategies and to identify the key factors for strain selection.Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 37 publications
(67 reference statements)
0
8
0
1
Order By: Relevance
“…Hence, the development of more robust strains that are still capable of producing a high-quality end product is a prime focus in biotechnology (Kim et al ., 1996; Perez-Torrado et al ., 2002, 2010; Panadero et al ., 2007; Kaino et al ., 2008; Gomez-Pastor et al ., 2012). For example, using an inverse metabolic engineering approach, Perez-Torrado et al .…”
Section: Genetic Modificationmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, the development of more robust strains that are still capable of producing a high-quality end product is a prime focus in biotechnology (Kim et al ., 1996; Perez-Torrado et al ., 2002, 2010; Panadero et al ., 2007; Kaino et al ., 2008; Gomez-Pastor et al ., 2012). For example, using an inverse metabolic engineering approach, Perez-Torrado et al .…”
Section: Genetic Modificationmentioning
confidence: 99%
“…For example, using an inverse metabolic engineering approach, Perez-Torrado et al . (2010) identified two genes, CAF19 and ORC2 , important for osmotolerance. Overexpression of these genes exerted a positive impact on the leavening activity of baker's yeast.…”
Section: Genetic Modificationmentioning
confidence: 99%
See 1 more Smart Citation
“…This is at least partly due to the technical difficulties associated with isolating representative cell samples from the solid fermentation matrix. Some studies have attempted to gain insight into bread fermentation by mimicking the process in liquid (15)(16)(17). Whereas such studies definitely contributed to our knowledge, they change the single most important parameter of SSFs (the solid state) and are therefore not an optimal model for the industrial SSF process.…”
mentioning
confidence: 99%
“…Several studies have investigated the expression profile of yeast genes during liquid fermentation such as beer, wine, or even liquid model dough fermentation (15,16,(18)(19)(20)(21)(22)(23). Those studies showed that in general, the start of fermentation is associated with a loss of stress resistance due to the repression of stress-related genes by glucose or sucrose (24)(25)(26).…”
mentioning
confidence: 99%